2016
DOI: 10.4103/0366-6999.172570
|View full text |Cite
|
Sign up to set email alerts
|

Underlying Mechanisms of Memory Deficits Induced by Etomidate Anesthesia in Aged Rat Model

Abstract: Background:Etomidate (R-1-[1-ethylphenyl] imidazole-5-ethyl ester) is a widely used anesthetic drug that had been reported to contribute to cognitive deficits after general surgery. However, its underlying mechanisms have not been fully elucidated. In this study, we aimed to explore the neurobiological mechanisms of cognitive impairments that caused by etomidate.Methods:A total of 30 Sprague-Dawley rats were used and divided into two groups randomly to receive a single injection of etomidate or vehicle. Then, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Similar was observed in animal studies. It does not seem to affect MDA levels or change SOD activity ( 57 ) in rat brain, while it significantly decreased MDA and increased GSH levels in the spinal cord after injury ( 58 ).…”
Section: Intravenous Anaestheticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar was observed in animal studies. It does not seem to affect MDA levels or change SOD activity ( 57 ) in rat brain, while it significantly decreased MDA and increased GSH levels in the spinal cord after injury ( 58 ).…”
Section: Intravenous Anaestheticsmentioning
confidence: 99%
“…In adult male rats it also increased MDA in the lungs, but decreased it in the kidney and brain ( 67 ). It also significantly reduced liver MDA levels in rats with ischaemia/reperfusion injury ( 57 ). Compared to isoflurane in another study ( 68 ), it produced significantly lower TBARS levels.…”
Section: Inhalational (Volatile) Anaestheticsmentioning
confidence: 99%
“…For instance, Chastain-Potts et al showed that sevoflurane exposure induces upregulation of Arc and Jun-B mRNA expression in the subiculum, which is crucial for synaptic plasticity and normal neuronal development [ 11 ]. Etomidate reduces the protein expression levels of memory-associated IEG in the rat hippocampus, including Arc, c-fos, and Egr1 [ 13 ]. However, there is some evidence that reveals distinct expression patterns in IEG under the same stimuli.…”
Section: The Use Of Other Immediate Early Gene Products In This Fieldmentioning
confidence: 99%
“…It has been shown (16) that dexmedetomidine could improve the neuronal apoptosis caused by isoflurane in neonatal rats. In addition, Etomidate is a type of drug used for general anesthesia and sedation (17), which has the advantages of quick effect, short acting time and little effect on circulation.…”
Section: Introductionmentioning
confidence: 99%